IMPLEMENTASI APLIKASI “MITA TERAPI AUTIS” TERHADAP KEMAMPUAN DAYA TAGKAP VISUAL PADA ANAK AUTIS DI PUSAT LAYANAN DAN PENDIDIKAN INKLUSI (PLDPI) SURAKARTA - Excel Alpin Coriawan; Arya Kumara Adji; Yoga Arvian; Astri Charolina (JURNAL GAUNG INFORMATIKA, 2019)
This research is a research related to how to utilize digital media technology through multimedia applications "MITA THERAPY AUTISM",so that it can be used by educators,to be applied as an application in supporting and optimizing therapeutic methods for children with special needs with autism disorders.This research was carried out directly in the scope of PLDPI SURAKARTA. Achievements obtained from the results of this study that the design can be used by teachers and have a positive effect on the development of students who experience autism disorders.In this research process, several suggestions and conclusions were made that the design and implementation of multimedia application-based learning can be used as a means to support learning and therapy needs for children with needs who experience autism disorders, especially in helping to increase the visual comprehension of students.